Pengaruh Pemberian Pupuk Hayati Terhadap Pertumbuhan dan Hasil Tanaman Bayam Brazil (Alternanthera sissoo) - afandi, subhan affan; Soeparjono, Sigit (Jember University Press, 2024)
ABSTRACT Spinach plant production has decreased every year and the use of inorganic fertilizers is still often used by farmers. The right innovation of Brazilian spinach cultivation technique is by using biological fertilizers. This study used a non-factorial completely randomized design (CRD) with 5 treatment levels repeated 4 times, namely C0: 0 mg/plant (Control), C1: 20 mg/plant, C2: 40 mg/plant, C3: 60 mg /plant, and C4: 80 mg/plant so that there are 20 experimental treatment units. The variables used in this study were plant height, number of leaves, number of branches, leaf area, chlorophyll content, canopy area, and plant fresh weight. The data obtained were analyzed for variance (ANOVA) and further tested with Duncan's Multiple Range Test (DMRT) with a confidence level of 95%. The results showed that there was a significant effect of the application of biological fertilizers on the growth and yield of Brazilian spinach (Althernanthera sisso), namely height plants that produce the highest average value of 24.23 cm, the variable number of branches with the highest value is 6.25 branches, the variable leaf area with the highest value is 131.88 cm2, and the variable number of leaves that gives a very significant different effect with the highest value ie 11.25 strands. The correct dosage of biological fertilizers is found in the Agrice Plus fertilizer treatment with a dose of 80 mg/plant for all observed variables. Keywords:, Brazilian Spinach, Biofertilizer